Advertising : concept and copy - Felton, George, 1947- (New York W. W. Norton & Company, 2013)
This book shows how to find strong selling ideas and how to express them in fresh, memorable, persuasive ways. The new edition features greatly expanded discussions of guerrilla advertising, interactive advertising, brand voice, storytelling, and the use of social media. Hundreds of ads in full color, both in the book and on an accompanying Web site, demonstrate the best in television, radio, print, and interactive advertising. Advertising: Concept and Copy is the most comprehensive text in its field, combining substantial discussion of both strategy and technique with an emphasis on the craft of writing not found elsewhere.
Keywords: Publicidad